2016
DOI: 10.1055/s-0036-1584523
|View full text |Cite
|
Sign up to set email alerts
|

Women's Experiences with and Preference for Induction of Labor with Oral Misoprostol or Foley Catheter at Term

Abstract: Objective We assessed experience and preferences among term women undergoing induction of labor with oral misoprostol or Foley catheter. Study Design In 18 of the 29 participating hospitals in the PROBAAT-II trial, women were asked to complete a questionnaire within 24 hours after delivery. We adapted a validated questionnaire about expectancy and experience of labor and asked women whether they would prefer the same method again in a future pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…However, our study did have participants with positive attitudes toward induction, similar to other studies 24 . Few studies have asked patients about specific labor induction interventions 11,25–27 . However, one study found that compared to oral misoprostol, more women in the Foley catheter group would prefer to receive a different method in the future 27 .…”
Section: Discussionsupporting
confidence: 65%
“…However, our study did have participants with positive attitudes toward induction, similar to other studies 24 . Few studies have asked patients about specific labor induction interventions 11,25–27 . However, one study found that compared to oral misoprostol, more women in the Foley catheter group would prefer to receive a different method in the future 27 .…”
Section: Discussionsupporting
confidence: 65%
“…The references have been assessed but not incorporated into the review. Only seven of these trials are likely to contribute data for this review and are mainly small trials (Khatib 2019; Lim 2018; Osoti 2018; Souizi 2018; ten Eikelder 2017; Tulek 2018; Viteri 2019). We imputed the data for these trials and this resulted in no changes in terms of the direction or strength of the evidence.…”
Section: Resultsmentioning
confidence: 99%
“…30 33 34 42 43 52 53 63 74 None of the trials used a validated patient-reported outcome instrument for labor induction; however, until very recently, there have been no validated questionnaires for labor induction. 101 While WHO and NICE guidelines recommend that patient needs and preferences be taken into consideration when selecting a method of labor induction, ACOG guidelines do not specify that maternal preference be considered. 2 4 In cases, in which labor induction methods have similar efficacy and safety profiles, we recommend that physicians and health care providers take into account patient preference and overall labor experience.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…2 4 In cases, in which labor induction methods have similar efficacy and safety profiles, we recommend that physicians and health care providers take into account patient preference and overall labor experience. 101 102…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%